Experiential Quality has the Potential to Mediate TPB in Generation Z’s Revisit Intention with Co-Creation Moderation - Rendi Fajar Utama Edri; Surya Bintarti; Anna Wulandari (Jurnal Ilmiah Manajemen Kesatuan, 2026)
The rapid development of VoD services has triggered changes in Generation Z consumption behavior and uncertainty regarding the factors that drive their intention to resubscribe. This study examines the behavior of Generation Z consumers who use Video on Demand (VoD) services Netflix, Disney+, and Viu in terms of revisit intention, considering the role of experiential quality as a mediating variable and co-creation (represented by product variation) as a moderating variable. The research approach uses a quantitative method with a purposive sampling technique on 570 VoD user respondents. Data analysis was conducted using Partial Least Square (PLS) regression with the help of SmartPLS 3 software. This study found that subjective norms and attitudes have a positive and significant effect on revisit intention among Netflix, Viu, and Disney+ users, while behavioral control only has an effect on Netflix and Viu. Experiential quality mediates some relationships for Netflix and Disney+, but is not significant for Viu, and product variation does not moderate its effect on revisit intention. These results indicate that social influence, positive attitudes, and quality of experience drive Gen Z’s revisit intention on VoD services, while product variation has a minimal role.